Online Bakery Shop System (OBSS) / Ong Tern Chow - Ong, Tern Chow (2003)
Online Bakery Shop System (OBSS) is an internet-based electronic commerce system developed with the objective of providing purchase and management service through World Wide Web. It is an application that makes use of the web multiple-tier client/server architecture. OBSS can be divided into 2 modules, which are the shopper and administrator module. The shopper module will provide facilities to the customer to brows and order cakes online. Shopper can also choose the cake clothing they prefer. Besides, shopper module will provide bakery lesson with different recipe and instructions to the shopper. In the administrator module, administrator can view, edit, update and delete records in the database. In addition, administrator is able to do business analysis by using OBSS. The system architecture of OBSS can be divided into client, web server and database server. The client which is the web browser can access information by connecting to the web server. Whenever the client wants to retrieve information from the database server, it has to submit the request to the web server that will interact with the database server. The database server process the request and result is sent back to the web server and finally to the client. OBSS is develop using Microsoft Visual Studio.NET technologies on the Microsoft Windows 2000 Server platform, utilizing database created by Microsoft SQL Server 7.0. Since current client/server based database system will be transforming to web-based database system, thus the system of this nature will become essential to everyone in the future.